Evaluation of Internal Control over Recurring Audit Findings of the Inspectorate General of the Ministry of Home Affairs - Yosef Gilbert Parhula Aruan; Udaya Madjid; Rusmiyati Rusmiyati (Sean Institute, 2026)
The achievement of public accountability in government institutions depends on the effective implementation of the Government Internal Control System (SPIP). Institutionally, the Ministry of Home Affairs (MoHA) has attained SPIP Maturity Level 3; however, recurring audit findings continue to be identified. This study aims to evaluate the effectiveness of the internal control system in addressing recurring findings, identify the inhibiting factors based on the five dimensions of the COSO framework, and formulate tactical recommendations to overcome these challenges. This descriptive qualitative study employed a case study approach. Data were collected through in-depth interviews with key informants representing both auditors (the Inspectorate General of the Ministry of Home Affairs) and auditees (the Directorate General of Village Government Development, the Regional Representative Council, the Institute of Public Administration Jatinangor Campus, and the Institute of Public Administration North Sulawesi Regional Campus), as well as through document analysis of the Audit Reports for the 2021–2024 period obtained from the SIWASIAT application. Data were analyzed using the Miles, Huberman, and Saldaña interactive analysis model. Using the five dimensions of the COSO framework as the analytical basis, the study identified five cross-dimensional and thematic inhibiting factors: weak organizational commitment and control culture; inadequate supervisory planning documents in determining the focus of recurring findings; regulatory weaknesses and the absence of enforceable institutional sanctions; limitations in supervisory information systems and technology; and weaknesses in monitoring methodology, along with a compliance-oriented approach to follow-up verification. The findings indicate that the current internal control system remains insufficient to break the cycle of recurring audit findings. Therefore, the study recommends strengthening leadership commitment through behavioral regulations, formalizing operational risk registers, enhancing the SIWASIAT early warning system, standardizing Root Cause Analysis (RCA) training for auditors, and implementing a two-step follow-up verification mechanism.